Acupuncture as prophylaxis for chronic migraine: a protocol for a single-blinded, double-dummy randomised controlled trial. Issue 5 (31st May 2018) - Liu, Lu; Zhao, Luo-peng; Zhang, Claire Shuiqing; Zeng, Lin; Wang, Kelun; Zhao, Jingxia; Wang, Linpeng; Jing, Xianghong; Li, Bin
Abstract : Introduction: Approximately 1.4%–2.2% of the global population suffers from chronic migraine. Acupuncture may serve as an alternative management for chronic migraine, where pharmacological prophylaxis is not suitable. However, the effects of acupuncture as migraine prophylaxis have not been confirmed. This study is designed as a single-blinded, double-dummy randomised controlled trial to evaluate the efficacy and safety of acupuncture compared with topiramate in patients with chronic migraine. Methods and analysis: A total of 60 participants will be randomly assigned to two different groups. Participants will receive verum acupuncture and placebo medicine in the treatment group, while participants in the control group will be treated with sham acupuncture and real medicine (topiramate). All participants will receive a 12-week treatment and then be followed up for another 12 weeks. The primary outcome is the reduction of monthly headache days, and the secondary outcomes include the reduction of the number of days with acute headache medications, and changes of Migraine Disability Assessment, Migraine-Specific Quality of Life Questionnaire, Headache Impact Test, State-Trait Anxiety Inventory-trait, and Beck Depression Inventory-II scores from baseline to endpoints. Ethics and dissemination: Ethical approval of this study was granted by the Research Ethical Committee of Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University (2017BL-045-01). Written informed consent will be obtained from all participants. Outcomes of the trial will be disseminated through peer-reviewed publications. Trial registration number: ISRCTN13563102; Pre-results .